Analysis of Multicultural Behavior of Senior High School Students - Yosef Yosef; Rahmi Rahmi; Astri Chya; Shelliataprimande Shelliataprimande; Nawang Julia Putri; Tengku Shaffaris Tanury (STAI Hubbulwathan Duri, 2023)
Adequately student multicultural behavior was one of the indicators of successful schooling. Presumably, the students who lived in rural or small city areas had less opportunity to interact with culturally diverse peers. This study aimed to examine their multicultural behavior in the school environment. Using a survey procedure quantitative approach, involved 100 respondents selected randomly, consisting of 34 in 10th grade, 32 in 11th grade, and 34 in 12th graders in Batumarta, a small city in South Sumatera Province, Indonesia. Data of students’ multicultural behavior were obtained by administering a questionnaire, a self-report four scales of Likert. It consisted of 36 items assessing their expressing multicultural behavior in five dimensions. For data analysis, after managing the ordinal data and converting them into interval data, we used a line chart to display the students’ multicultural behaviors according to their frequencies in each dimension and compared mean scores of multicultural behaviors based on gender and grade levels by using the analysis of variance method. In conclusion, we found most students have a moderate frequency in expressing multicultural behavior, male and female students had dissimilar multicultural behavior, there were no multicultural behavior differences among the three grade levels, and the predominantly ethnic students were not different from their peers. Finally, we recommended the school develop a multicultural behavior program.